Quantity-based or share-based? Discount schemes for the manufacturer when facing two competing retailers - Wenhui Zhou; Hongmei Yang (Modern Supply Chain Research and Applications, 2023)
Purpose – The authors investigate the manufacturer's choice of discount schemes in a supply chain with competing retailers. Design/methodology/approach – Using a game-theoretic model, the authors build two discount frameworks and compare and analyze the effects of different discount schemes on the performance of supply chain members. Findings – The authors find that the retail price (market demand) in the quantity discount scheme is always higher (lower) than that in the market share discount scheme. The authors also find that the retailers' preference for discount schemes is antithetical to the manufacturer's preference in most cases. However, under certain conditions, there will be a win-win situation where Pareto-optimization occurs between the manufacturer and retailers when they choose the same discount scheme. Research limitations/implications – On the one hand, the authors assume that the two retailers are symmetrical in market size and operation efficiency. It would be interesting to study the effect of different discount schemes on retailers when the retailers have different market sizes or operating efficiency. On the other hand, the authors study the manufacturer's choice of discount schemes in a supply chain with one common manufacturer and two competing retailers. However, in practice, there exist other supply chain structures. Future research can examine the problem of choices of discount schemes in other different supply chain structures. Practical implications – This paper help retailers and manufacturers to choose the best discount schemes. Social implications – This paper suggests that a high discount scale is not always beneficial (detrimental) to retailers (the manufacture). Originality/value – The authors build two discount schemes (the quantity and the market share) in a supply chain consisting of one manufacturer and two retailers, and the authors focus on the effects of different discount schemes on the competition between two retailers. By comparing the two discount schemes, the authors study which discount scheme is the better choice for the manufacturer when facing competing retailers.